Hubungan Aktivitas Fisik, Konsumsi Cairan, Status Gizi Dan Status Hidrasi Pada Pekerja Proyek - Ferlica Pustisari; Laras Sitoayu; Rachmanida Nuzrina; Dudung Angkasa; Nazhif Gifari (Universitas Muhammadiyah Semarang, 2020)
Hydration status is a condition that describes the amount of fluid in the body. If the intake of fluids from food and drinks in the project workers is not met, then it has an opportunity to cause dehydration. Declining productivity in workers can be caused by dehydration. Objectives this study to determine the relationship between physical activity, fluid intake, nutritional status and hydration status in project workers. An observational study with a cross sectional approach, the study population was project workers. The number of samples in this study were 53 respondents. The study was conducted by direct interview, measurement of body weight,height, body fat percent and urine specific gravity. Data analysis in this study used the Spearman correlation test. The age of workers ranged from 17-52 years. The average BMI score was22,417 kg / m2.The average value of PAL 2.37. The average fluid intake was 2018.30 ml. Moyority of workers have hydration status in severely dehydrated group (79.2%.) There is a relationship between physical activity (0.026), fluid intake and hydration status (0.001) but there is no relationship between nutritional status and hydration status (0.789). Keywords: fluid intake; nutritional status; physical activity; hydration status.